The Effects of Early Retirement Incentives on Retirement Decisions - Mathias Dolls; Carla Krolage (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper analyzes behavioral responses to a reform in the German public pension system that allowed individuals with a long contribution history to retire without deductions before reaching the regular retirement age. Following the 2014 reform, individuals with 45 contribution years could retire without deductions as early as age 63 instead of age 65. Using high-quality administrative data from public pension insurance accounts, we first conduct an event study to quantify responses to becoming eligible for the early retirement scheme. Our results indicate that the probability of retiring immediately increases by more than 10 percentage points upon becoming eligible, relative to the counterfactual probability of retiring at the same age with deductions. Second, we employ a coarsened exact matching procedure to compare retirement entry decisions of eligible and non-eligible individuals. Results are in line with the event study and show that individuals who are eligible for the early retirement scheme retire on average 5.4 months earlier than non-eligible individuals with identical characteristics. With additional pension insurance expenditures of 3.4 billion euro and aggregate fiscal costs of 6.5 billion euro in 2016, our subsequent fiscal cost projections are at the upper end of the range of previous back-of-the-envelope estimates.
Keywords: H55; J14; J18; J26; 330; Retirement age; early retirement; pension reform